Pemetaan Literatur pada Industri Jasa Kebersihan di Indonesia dari Tahun 2010 Sampai Dengan 2021 - Tri Hadi Sulistyanto; Masydzulhak Djamil; Ahmad Hidayat Sutawidjaya; Lenny Christina Nawangsari; Ahmad Badawi Saluy; Indra Siswanti (Jurnal Doktor Manajemen (JDM), 2022)
The importance of cleaning services are considered to be more and more important because at all times a clean and healthy environment is needed. The cleaning service industry is closely related to room and environment cleanliness, such as in hospitals, hotels, office buildings, to residential areas. However, positions in cleaning service industry are less attractive to workers. One of the important questions that has to be answered is whether the importance of work in the cleaning service industry is also in line with the number of research conducted in cleaning service industry. This literature mapping aims to find out how many scientific articles related to this industry, especially the ones from Indonesia who are indexed by various scientific literature search sites on the internet. This paper is also useful to provide a reference for researchers who will conduct research on this industry in Indonesia. The data showing that total research publications on the cleaning service industry by researchers from indonesia are relatively same compared to the literature on the same industry published by researchers from abroad. However, the literature published by researchers from Indonesia in English is still relatively a few compared to the literature published in Indonesian language.The importance of cleaning services are considered to be more and more important because at all times a clean and healthy environment is needed. The cleaning service industry is closely related to room and environment cleanliness, such as in hospitals, hotels, office buildings, to residential areas. However, positions in cleaning service industry are less attractive to workers. One of the important questions that has to be answered is whether the importance of work in the cleaning service industry is also in line with the number of research conducted in cleaning service industry. This literature mapping aims to find out how many scientific articles related to this industry, especially the ones from Indonesia who are indexed by various scientific literature search sites on the internet. This paper is also useful to provide a reference for researchers who will conduct research on this industry in Indonesia. The data showing that total research publications on the cleaning service industry by researchers from indonesia are relatively same compared to the literature on the same industry published by researchers from abroad. However, the literature published by researchers from Indonesia in English is still relatively a few compared to the literature published in Indonesian language.